Pengaruh Digitalisasi dan Pandemi COVID-19 Terhadap Pembentukan Keterampilan Guru di Jepang - Stahlumb, Frichicilia Grace; Iskandar, Kurniawaty (KIRYOKU, 2024)
This paper examines how the COVID-19 pandemic has implications for the formation of Japanese teachers' skills related to digitalisation, as well as how the teaching and learning situation in Japan has changed as a result. The COVID-19 pandemic has indirectly forced teachers in Japan to adapt and change their teaching methods to students. Discussions on teacher certification and training in Japan, digitization of education in Japan, and the formation of teacher skills in Japan before and after the COVID-19 pandemic are used to explain how digitization was already introduced in education in Japan but was only massively implemented during the COVID-19 pandemic. The results of this study found that current teacher skills in Japan have undergone some changes in standards. The introduction of digitalization in education in Japan as well as the COVID-19 pandemic that entered Japan in 2020 indirectly changed the teaching standards of teachers in Japan. Nowadays, teachers in Japan are not only required to be proficient in teaching but also to act as practitioners in their teaching environment, thus indirectly changing the teaching and learning process in Japan.